2022
DOI: 10.1136/spcare-2022-003861
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivor inspiratory muscle training: systematic review and Bayesian meta-analysis

Abstract: BackgroundThe long-term impact of cancer treatment is associated with respiratory dysfunction and physical fitness impairment. Although inspiratory muscle training (IMT) has been shown as an effective exercise therapy in cancer survivors, there is no evidence on the optimal dose, application moment nor specific population effects of this intervention. The main objective of this meta-analysis is to analyse the effects of IMT on pulmonary function, physical fitness and quality of life (QoL) in cancer survivors.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Physical training has been widely used in respiratory rehabilitation. In fact, some systematic reviews have shown that respiratory muscle training improves several pulmonary function parameters and maximal static pressures in some clinical populations such as patients with chronic obstructive pulmonary disease [26], lung cancer survivors [27], asthma [28], obstructive sleep apnea [29], or tobacco smokers [30,31]. Therefore, we believe that the addition of mental practice along with the performance of respiratory muscle training could have an impact on these clinical populations.…”
Section: Introductionmentioning
confidence: 93%
“…Physical training has been widely used in respiratory rehabilitation. In fact, some systematic reviews have shown that respiratory muscle training improves several pulmonary function parameters and maximal static pressures in some clinical populations such as patients with chronic obstructive pulmonary disease [26], lung cancer survivors [27], asthma [28], obstructive sleep apnea [29], or tobacco smokers [30,31]. Therefore, we believe that the addition of mental practice along with the performance of respiratory muscle training could have an impact on these clinical populations.…”
Section: Introductionmentioning
confidence: 93%
“…In patients with cardiopulmonary diseases, the scientific clinical literature on the efficacy of RMT in reducing dyspnea is compelling [ 19 , 45 - 47 , 49 , 51 ]. However, in patients with cancer, the evidence for RMT efficacy is preliminary, insufficient and with many gaps [ 10 - 13 , 65 ]. Randomized controlled trials of RMT interventions are warranted in patients with different types of cancer and dyspnea.…”
Section: Future Research Directions and Conclusionmentioning
confidence: 99%
“…In a recent systematic review, Meneses-Echavez et al reported that the minimum clinically important difference in strength is between 5 and 6.5 kg [14]. Regarding functional outcomes, the effect of inspiratory muscle training can be measured by inspiratory muscle pressures, forced vital capacity, and forced expiratory volume in 1 s [86].…”
Section: How Is the Effect Of A Prehabilitation Strategy Measured?mentioning
confidence: 99%